Building a Conceptual Framework from Polyvagal Theory to Explore Effect of Maternal Speech on Neural Development in Premature Infants - Bubshait, Khlood (Journal of Biology and Life Science, 2021)
The objective of this review was to evaluate the application of Polyvagal theory to: (1) explore relationships between maternal speech and neural development in premature infants; (2) explain influences of moderators, mediators, and confounding variables of early developmental exposure to maternal speech on neural development in premature infants. A positivist ontological approach was undertaken to explore and evaluate the application of Polyvagal theory in the research area of the effect of maternal speech on neural development or heart rate variability in premature infants. The Polyvagal theory was determined to be an effective theory for describing the effect of early developmental exposure to maternal speech on neural development. Major propositions are presented based on the proposed conceptual model, which integrates previous research on exposure to maternal speech, to ultimately enhance neural development in premature infants.